Carcinoid Heart Disease: Starting From Heart Failure - Nicole Bertin MD; Serena Favretto MD; Francesco Pelizzo MD; Lucio Mos MD; Franco Pertoldi MD; Olga Vriz MD (SAGE Publishing, 2017)
Carcinoid syndrome is the constellation of symptoms mediated by humoral factors produced by some carcinoid tumors. It consists primarily of vasomotor symptoms, gastrointestinal hypermotility, hypotension, and bronchospasm, due to the production and release of vasoactive substances. Carcinoid heart disease occurs in more than 50% of patients with carcinoid syndrome; in some cases, it represents the initial manifestation of the disease. We report the case of a 75-year-old woman with a metastatic neuroendocrine tumor admitted to the emergency room for fatigue and heart failure. Transthoracic echocardiography showed severe tricuspid and pulmonic regurgitation suggesting carcinoid heart disease. A hypervascular retroperitoneal mass was found on abdominal computed tomography, which seemed to arise from the mesenteric artery, anteriorly to the abdominal aorta. Unfortunately, our patient was neither a candidate for mass resection nor for cardiac surgery due to advanced metastatic disease and poor clinical condition. Additionally, we performed a systematic literature review of carcinoid heart disease focusing on typical echocardiographic findings.